Relationship between Waiting Time at the Registration Desk and Patient Satisfaction at Ngebel Ponorogo Health Center - Dea Nisa' Istiqomah (Garuda Pelamonia Jurnal Keperawatan, 2025)
Dea Nisa' Istiqomah, 2025. "The Relationship Between Waiting Time at the Registration Point and Patient Satisfaction at the Ngebel Ponorogo Health Center". Scientific Paper, Supervisor: Ucik Ernawati, S.Kep., Ns., M.Kes. DIII Medical Records and Health Information Study Program, STIKes Buana Husada Ponorogo. The waiting time at the registration section is one of the key factors in patient satisfaction in getting services at the Health Center. This study aims to analyze the relationship between the waiting time at the registration section and patient satisfaction at the Ngebel Ponorogo Health Center.The study used a quantitative correlational method using the Spearman rank test in SPSS. Data were obtained from filling out a questionnaire by 78 patients as respondents with 15 questionnaire questions. The results of the Spearman rank test showed rho 0.645 and p-value 0.000 <0.005 which can be interpreted that the length of waiting time and patient satisfaction in the registration section of the Ngebel Health Center in this study correlated with a strong relationship.The conclusion of this study is that there is a significant relationship between the length of waiting time for service and patient satisfaction. It is recommended that the health center complete the facilities and infrastructure and improve discipline so that it can provide satisfactory service when patients register, with the hope that the quality of health center services can improve.